Harmonics or the philosophy of musical sounds - Smith, Robert (New York Da Capo Press, 1966)
1966 FACSIMILE from1749 , Cambridge , England by R Smith DD FRS. "For scholars interested in music rather than for musicians" - quote from 1966 Intro. by J Murray Barbour Michigan State University
original print see 09J03